The Effect of Firm Size, Firm Age, Profitability, and Leverage on Corporate Social Responsibility Disclosure - Tarindra Ardhiningtyas; I Made Pande Dwiana Putra (International Forum of Researchers and Lecturers, 2025)
Corporate Social Responsibility disclosure reflects the extent to which a company communicates its overall responsibility for the impact of its activities in order to achieve business sustainability. This study aims to empirically examine the effect of firm size, firm age, profitability, and leverage on Corporate Social Responsibility disclosure. The research sample consists of energy sector and basic materials sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period that reported annual reports and sustainability reports using the GRI 2021 standards. The sampling method employed purposive sampling, resulting in a total of 33 companies with 99 observations. Data analysis was conducted using multiple linear regression analysis. Based on the analysis results, it can be concluded that firm age and profitability have a positive effect on Corporate Social Responsibility disclosure. Firm size and leverage do not have an effect on Corporate Social Responsibility disclosure. This study provides empirical evidence for Legitimacy Theory in explaining how internal company factors, particularly firm age and profitability, affect Corporate Social Responsibility disclosure as a form of aligning corporate activities with prevailing values and norms as well as societal expectations to obtain and maintain social legitimacy.